1978
DOI: 10.1017/s0021859600048590
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein content and the subsequent body composition and food intake of pigs

Abstract: SUMMARYForty Large White × Wessex pigs were fed from 7 to 27 kg live weight, on diets containing either 28 or 14% crude protein. From 27 to 113 kg live weight the pigs were fed a common diet ad libitum. Pigs from each treatment were killed at 27, 54, 82 and 113 kg live weight and the chemical composition was determined. From 7 to 27 kg and from 27 to 113 kg live weight, daily gain, food intake and food conversion efficiency were similar for the two treatments.At 27 kg, pigs on the lower protein diet were fatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…By using all 244 pigs in regression analyses it was found that the deposition of 1 g protein increased live weight by 5.8 g, and deposition of 1 g chemical fat increased live weight by 3.4 g. Investigations of the regression coefficients at 20 kg and 90 kg live weight indicated a positive quadratic term. WYLLIE and OWEN (1978) found that a quadratic term in the statistical model did not contribute much in explaining the total variation, when the content of protein and chemical fat was regressed against weight of empty body. The large variation in chemical composition of the pigs and of gut fill (2.4 kg to 10.0 kg at 90 kg live weight) on which the regression coefficients are based make them usable for control of balance experiments.…”
Section: Interrelationship Between Different Anatomical Fractions Andmentioning
confidence: 94%
“…By using all 244 pigs in regression analyses it was found that the deposition of 1 g protein increased live weight by 5.8 g, and deposition of 1 g chemical fat increased live weight by 3.4 g. Investigations of the regression coefficients at 20 kg and 90 kg live weight indicated a positive quadratic term. WYLLIE and OWEN (1978) found that a quadratic term in the statistical model did not contribute much in explaining the total variation, when the content of protein and chemical fat was regressed against weight of empty body. The large variation in chemical composition of the pigs and of gut fill (2.4 kg to 10.0 kg at 90 kg live weight) on which the regression coefficients are based make them usable for control of balance experiments.…”
Section: Interrelationship Between Different Anatomical Fractions Andmentioning
confidence: 94%
“…In some instances, rate of weight gain does not provide a good measurement of amino acid adequacy because of variations in composition of gain with age and/or dietary balance (Hogberg and Zimmerman, 1979). In the growing animal, direct or indirect assessment of protein gain provides a more precise assessment of amino acid adequacy (Brown et al, 1951;Smith et al, 1967;Wyllie and Owen, 1978) than does body weight gain.…”
Section: Production Traitsmentioning
confidence: 99%
“…This measurement, however, requires the use of laborious and expensive comparative slaughter techniques (Brown et al, 1951;Wyllie and Owen, 1978). Brown et al (1973) concluded that growth rate is a relatively poor indicator of amino acid requirements for lean meat production and it gives lower requirement estimates than feed conversion ratio or lean tissue deposition.…”
Section: Criteria To Estimate Amino Acid Requirements For Growth Perfmentioning
confidence: 99%